(untitled) (Journal of Medical & Health Sciences Review, 2025)
Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder among women of reproductive age, often associated with metabolic, reproductive, and anthropometric abnormalities due to underlying insulin resistance. This study aimed to compare the efficacy of myoinositol and metformin—two insulin-sensitizing agents—in the management of PCOS. A randomized controlled trial was conducted over eight months at the Department of Obstetrics & Gynaecology, SMBBMU, Larkana, Pakistan. Eligible patients were randomly assigned to receive either myoinositol or metformin and were followed up at two-month intervals over a six-month treatment period. The mean age in the myoinositol group was 26.6 ± 5.1 years, while in the metformin group it was 27.1 ± 4.9 years. Myoinositol was found to be effective in 23 (65.7%) patients compared to 9 (25.7%) in the metformin group, with a statistically significant difference (p = 0.001). These findings suggest that myoinositol may offer superior efficacy compared to metformin in managing PCOS. However, further research is warranted to account for potential residual confounding factors and to confirm these outcomes in larger populations.